Ultrasound‐guided percutaneous needle tenotomy (PNT) alone versus PNT plus platelet‐rich plasma injection for the treatment of chronic tendinosis: A randomized controlled trial. Issue 12 (28th April 2021) - Kirschner, Jonathan S.; Cheng, Jennifer; Hurwitz, Nicole; Santiago, Kristen; Lin, Emerald; Beatty, Nicholas; Kingsbury, Dallas; Wendel, Ian; Milani, Carlo
Abstract: Background: Tendinosis is a chronic degenerative condition. Current research suggests both percutaneous needle tenotomy (PNT) and leukocyte‐rich platelet‐rich plasma (LR‐PRP) may be effective treatments for chronic tendinosis, but no studies have assessed the effectiveness of PNT alone versus PNT with intratendinous LR‐PRP for multiple tendon types in a single study. Objective: To assess the efficacy of PNT versus PNT + LR‐PRP to treat chronic tendinosis. Study Design: Double‐blind, randomized, controlled comparative treatment study. Setting: Primary academic institution. Participants: A convenience sample of 40 participants who had chronic tendinosis (rotator cuff, wrist extensor, wrist flexor, hip abductor, proximal hamstring, patellar, or Achilles) confirmed via ultrasound, failed conservative treatment, and did not have tendon tears, known coagulopathy, or systemic illnesses. Interventions: Participants were randomly assigned to PNT (n = 19) or PNT + LR‐PRP (n = 21). Participants and outcomes assessors were blinded to treatment assignments. PNT was performed with 20–30 passes of a 22‐gauge needle under ultrasound guidance, with 1% lidocaine given outside the tendon. LR‐PRP was processed from whole blood (30–60 mL) and injected into the affected tendon using the same PNT technique. Main Outcome Measures: Primary outcome was current numerical rating scale pain at 6 weeks. Secondary outcomes were average pain, function, general well‐being, and sleep quality at 6, 52, and 104 weeks. Results: Baseline characteristics were similar between groups. Overall, there were no significant differences between groups over time for any of the outcomes ( P > .05). Between‐group analyses showed significantly lower current and average pain after PNT compared to PNT + LR‐PRP at 6 weeks (estimated‐mean [SE]: 3.1[0.4] vs. 4.6[0.6], P = .04; 3.4[0.4] vs. 4.9[0.5], P = .03) only. Adverse event rates were low (PNT‐3.9%; PNT + LR‐PRP‐5.0%) and related primarily to postprocedural pain and inflammation. Conclusions: Although pain scores were lower after PNT compared to PNT + LR‐PRP at 6 weeks, there were no between‐group differences in outcomes at 52 or 104 weeks.